2005
DOI: 10.1111/j.1525-1470.2005.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Petechial Exanthem in “Bathing Trunk” Distribution Caused by Parvovirus B19 Infection

Abstract: We report a 13-year-old boy with a petechial rash on the genital area, in which primary infection by Parvovirus B19 was demonstrated by seroconversion. To our knowledge this is the first instance of an exanthem arising from Parvovirus B19 with an exclusive genital distribution without typical acral involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…These polymorphous purpuric-petechial eruptions caused by PVB19 are acute selflimiting illness often accompanied by fever and other systemic symptoms such as fatigue, myalgia, anorexia, lymphadenopathy and arthralgia. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21][22][23] In contrast to EI seen in the post-viremic phase, 24 purpuric-petechial eruptions are closely linked to the viremic phase of primary PVB19 infection. [2][3][4][5][6]8,[11][12][13][14][15][16][18][19][20][21][22] Therefore, patients with papular-purpuric eruptions caused by PVB19 are considered infectious when presenting with the rash.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These polymorphous purpuric-petechial eruptions caused by PVB19 are acute selflimiting illness often accompanied by fever and other systemic symptoms such as fatigue, myalgia, anorexia, lymphadenopathy and arthralgia. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21][22][23] In contrast to EI seen in the post-viremic phase, 24 purpuric-petechial eruptions are closely linked to the viremic phase of primary PVB19 infection. [2][3][4][5][6]8,[11][12][13][14][15][16][18][19][20][21][22] Therefore, patients with papular-purpuric eruptions caused by PVB19 are considered infectious when presenting with the rash.…”
Section: Discussionmentioning
confidence: 99%
“…Purpuric-petechial eruptions in exclusive intertriginous areas without typical acral involvement were also reported in PVB19 infected partients. 8,10 During the past two decades, only a few reports have described generalized papular-purpuric eruptions associated with PVB19 in the English literature. Six cases were reported with prominent acral and intertriginous distribution.…”
Section: Other Similar and Contrasting Cases In The Literaturementioning
confidence: 99%
“…immunohistochemistry still strongly support parvovirus B19 as the main etiologic agent of PPGSS [60].…”
Section: Negative Clinical Features • Extensive Truncal Lesions • Scamentioning
confidence: 97%
“…These parvovirus-associated hemorrhagic rashes seem to be uncommon, and published reports have described only solitary or sporadic cases (reviewed by McNeely et al 1 and additionally reported by others [2][3][4][5][6][7]. Most case reports emphasized the distinctively focal ("gloves and socks," 8 "bathing trunk," 5,7 or "acropetechial" 9 ) distribution of these atypical rashes, and only a few reports have described generalized petechial rashes associated with parvovirus infection. [1][2][3]10 We could find no description of an outbreak of parvovirus-associated petechial rash in the English-language medical literature.…”
mentioning
confidence: 91%